Pengabdian Kepada Masyarakat Melalui Perayaan Hari Santri Nasional Bersama Masyarakat Desa Bukit Permata - Hartono, Hartono; Sari, Luluk Nur Indah; Bunyamin, Khamal Al Kahfy; Asraf, Muhammad Aiman; Muhaqqiqoh, Seivi Sufiatul (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
National Santri Day is a moment to appreciate the contribution of santri in the nation's struggle. However, in some areas, this commemoration has not been fully utilized to strengthen the relationship between pesantren, the community, and the government. This service aims to optimize the commemoration of Santri Day in Bukit Permata Village with a collaborative approach involving various elements of society. The method used is Participatory Action Research (PAR), which involves active community participation in all stages of the activity. The results of this service strengthen relationships between villagers, increase togetherness, and strengthen a sense of pride in cultural and religious identity. National Santri Day celebration activities such as adhan competitions, quiz, tahfidz, coloring, and fashion shows can also increase community understanding of religion, culture, and education. The implication of this service is the creation of an inclusive, participatory, and sustainable Santri Day celebration model, which can be an inspiration for other regions in celebrating Santri Day in a more meaningful and sustainable manner.